Psychosophia Vol. 3, No. 1 (June 2021) full-text (all article) - Oktarizal Drianus (Department of Islamic Psychology, The State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, Indonesia, 2021)
In this June 2021 Edition (Vol. 3, No. 1), Psychosophia presents topics that are mostly related to the Muslim community. These publications include 1) Articles on the Happiness of Santri in Pesantren; 2) Articles that discuss the perception of caning as the application of Qonun Jinayah to the Muslim community in Aceh; 3) Another article is about burnout by gender. Articles that discuss academic stress include 4) Articles on religiosity and self-efficacy toward academic stress in college students; 5) Other articles discuss cruel behavior towards animals.